Sitting in limbo or being the flaming Phoenix: the relevance of the archival discipline to the admissibility of digital evidence in China - Weimei Pan; Luciana Duranti (Archives & Manuscripts, 2020)
This article presents a review of the progress made in the digital transition in China, especially in light of the fact that admissibility of digital records in legal proceedings is a critical factor in such transition. It discusses the Chinese legal system and the rules governing the admissibility of both paper and digital records as well as the reasons why evidence collection and preservation by a third party has become a popular approach to guarantee the integrity of the records and improve their chances of admissibility in a court of law. In this context, this article then discusses how the InterPARES Trust PaaST model can help address some of the issues, thus, demonstrating the relevance of archival knowledge to the digital transition.